High performance liquid chromatographic method for the determination of ambroxol hydrochloride in presence of antimicrobial preservatives in oral liquid formulation - Sudha, T; Manthena, K; Ravikumar, VR; Ganesan, V (Bangladesh Pharmaceutical Journal, 2015)
A simple gradient reversed phase high performance liquid chromatographic method was developed for the determination of ambroxol hydrochloride in presence of antimicrobial preservatives in oral liquid formulation. The chromatographic separation was achieved by an Inertsil C8 (250 X 4.6 mm, 5? particle size) column using gradient technique. The eluents were detected at 245 nm with photodiode array detector. The optimized mobile phase consisted of 0.1% trifluoroacetic acid as a mobile phase A and a mixture of mobile phase A and acetonitrile in the ratio of 76:24 % v/v as mobile phase B. Ambroxol hydrochloride and microbial preservatives were eluted at a flow rate of 1.0 ml/min. The method validated according to the International Conference of Harmonization (ICH) guidelines. The calibration curves were linear over the (r2 > 0.99) concentrations range from 300 to 900 ppm for ambroxol hydrochloride, 10 to 30 ppm for propyl paraben and 100 to 300 ppm for methyl paraben. The limit of detection was found to be 0.024 ppm for ambroxol hydrochloride, 0.018 ppm for propyl paraben and 0.009 ppm for methyl paraben. The percentage recoveries were found to be in the range from 99.55 to 101.1% for ambroxol hydrochloride, 100.31 to 101.46% for propyl paraben and 98.18 to 101.61% for methyl paraben. Stability indicating capability was established by forced degradation experiments. No chromatographic interference from the degradation products was found. The proposed method was highly sensitive, precision and accurate and hence successfully applied for the quantification of ambroxol active pharmaceutical ingredients (API) and preservatives content in the commercially available oral liquid formulation. Bangladesh Pharmaceutical Journal 18(1): 8-14, 2015